Guided Learning Model Raises Elementary Science Concept Mastery: Model Pembelajaran Terbimbing Meningkatkan Penguasaan Konsep Sains pada Tingkat Dasar - M.Aliffiyano Rozzaq; Fitria Wulandari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Concept mastery in elementary science learning is essential to develop students’ scientific reasoning and meaningful understanding of natural phenomena. Specific Background: Classroom practice often remains teacher-centered, resulting in passive participation and limited comprehension of core science concepts. Knowledge Gap: Although various instructional models and media have been reported, contextual evidence describing their classroom application and students’ conceptual outcomes remains limited. Aims: This study aims to describe the implementation of a guided learning model supported by instructional media and to examine students’ concept mastery within an elementary classroom. Results: Using educational research procedures with tests, observations, and documentation, the findings show increased student engagement, more active participation, and higher post-learning scores compared with initial performance. Structured activities, visual media, and collaborative tasks supported understanding, while time constraints and varied readiness posed challenges. Novelty: The study provides a detailed classroom-based account of model implementation combined with analysis of supporting and inhibiting factors. Implications: The results suggest that organized instructional design and appropriate media selection can support sustainable concept mastery in elementary science education. Keywords: Science Education, Concept Mastery, Elementary Students, Learning Model, Instructional Media Key Findings Highlights: Greater learner participation during instructional activities Posttest scores surpassed baseline achievement Classroom tools assisted clearer material comprehension